Efeito da quercetina na atividade de ectoenzimas e da acetilcolinesterase em sinaptossomas do córtex cerebral de ratos expostos ao cádmio - Abdalla, Fátima Husein (2012)
Cadmium (Cd) is one of the most toxic heavy metals by their ability to affect the vital organs like liver, kidney, brain and other. This metal can trigger a framework of oxidative stress by increase of reactive oxygen species and also affect cholinergic and purinergic neurotransmission. Quercetin (Querc), a flavonoid found in various foods has several functions in the body as a therapeutic antioxidant and neuroprotective action. The aim of this study was to evaluate the activity of ectoenzymes and acetylcholinesterase (AChE) activity in synaptosomes of the cerebral cortex of adult rats exposed to cadmium chloride at a dose of 2.5 mg/kg and treated with Querc at doses of 5, 25 and 50mg/kg, both solutions were orally administered in a volume of 1 mL/kg for 45 days. Results showed that the hydrolysis of ATP, ADP, AMP and ADA activity in the synaptosome cerebral cortex in the Cd/ethanol group increased compared to the saline/ethanol group (p<0.05). The treatment with all doses of Querc prevented the increase in the hydrolysis of ATP, ADP, and AMP as well as the ADA activity (p<0.05). In vitro assay with Querc 25 and 50 μM showed a decrease in the activities of these enzymes except of ADA (p<0.05). The AChE activity ex vivo was not significantly different in the Cd/ethanol group when compared to the saline/ethanol group. The treatment with Querc 25 and 50 mg/kg significantly decreased the AChE activity when compared to the Cd/ethanol group (p<0.05). In vitro assay showed a decrease in the AChE activity only with 100 and 200 μM of Querc (p<0.05). These results suggest that Querc prevented the alterations caused by Cd in purinergic and cholinergic system. Thus, the results reported here suggest that Querc is a promising compound that can be clinically investigated in order to be used in alternative therapies for the treatment of neurodegenerative diseases or brain diseases associated with poisoning by heavy metals.